Salmonellosis in buffaloes and cows with reference to reproductive failures - Verma, Shubhash; Katoch, R C; Nigam, Parag; Verma, J C; Nagal, K B (The Indian Journal of Animal Sciences, 2012)
The role of salmonellosis in causation of abortions and infertility was investigated in 43 buffaloes and 110 cows. The isolation was successful from single abortion in a buffalo that yielded Salmonella typhimurium while 2 out of 7 aborted cows had S. dublin. From uterine discharges of 33 endometritic cows 2 isolates of S. typhimurium were identified. None of 18 samples from endometritis in buffaloes, 24 normally cyclic repeat breeding buffaloes, 56 normally cyclic repeat breeding cows, 8 cases of cervicitis in cows and 6 cases of vaginitis in cows revealed Salmonella infection. The antibiogram against 16 chemotherapeutics was also studied.